Selective and Scalable Dehydrogenative Electrochemical Synthesis of 3,3′,5,5′-Tetramethyl-2,2′-biphenol - Selt, Maximilian; Mentizi, Stamo; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R. (Synlett, 2019)
3,3′,5,5′-Tetramethyl-2,2′-biphenol is a compound of high technical significance, as it exhibits superior properties as building block for ligands in the transition-metal catalysis. However, side reactions and overoxidation are challenging issues in the conventional synthesis of this particular biphenol. Here, an electrochemical method is presented as powerful and sustainable alternative to conventional chemical strategies, which gives good yields up to 51%. Despite using inexpensive and well-available bromide-containing supporting electrolytes, the issue of bromination and general byproduct formation is effectively suppressed by adding water to the electrolyte. Additionally, the scalability of this method was demonstrated by conducting the electrolysis on a 122 g scale.
Keywords: electrosynthesis; oxidation; phenol; anode; biphenol; sustainable synthesis